CULTURA DE APRENDIZAGEM UM DIFERENCIAL COMPETITIVO NAS ORGANIZAÇÕES - Ciliato, Sâmia Cristiane (2023)
The context of technological transformations that we are experiencing and the speed with which they occur, their impacts on the world economy, globalization, the volatility of capital and unbridled innovation are reasons for concern for leaders and organizations as a whole and this situation requires development continuous knowledge of the organization and consequently of people so that the organization remains competitive in the market. From the exposed context the following question arises: what factors enhance the organizational learning culture in a cooperative financial institution? To this end, the general objective of this study is to understand the factors that enhance the organizational learning culture in a cooperative financial institution, followed by the specific objectives that are: to analyze the relationship between organizational learning culture factors and organizational performance factors; verify the relationship between organizational culture and organizational learning culture; identify aspects of the organizational climate that contribute to fostering the organizational learning culture; map good practices for organizational learning culture factors that present opportunities for improvement in the overall score, determine whether all necessary elements are included in the Corporate Education strategy to achieve an organizational learning culture and correlate learning with the ability to organizational innovation. This research is a case study in a Cooperative Financial Institution that has been in the market for over 100 years. To do this, we will use the simplified version of the Learning Culture Measurement Scale, called Dloq-A, which seeks to measure how much culture is conducive to organizational learning. Furthermore, the documentary analysis is composed of the 2023 Innovation Census and the results of the Organizational Climate Survey for the year 2023. Among the results, it is identified that the learning culture is essential for the solidity of the business, so that the climate organization is satisfactory and to accelerate innovation. Furthermore, strategies identified to boost the organizational learning culture are the sharing of knowledge, experiences and good practices among employees, part of an education strategy that needs to consider strategic planning, business challenges and development needs. of employees. Furthermore, it is essential that learning is encouraged daily, as a continuous process and part of the work routine, providing practices and experiences in a systematic, strategic and integrated way with the organizational reality.